Biomechanical comparison of different bilateral percutaneous vertebroplasty in treating osteoporotic vertebral compression fractures: finite element analysis - Yang, Weihua; Chen, Jing; Lin, Bei; Feng, Eryou (Frontiers in Surgery, 2025)
PurposeThis study aimed to analyze the biomechanical effects of two bone cement injection techniques by establishing a finite element model of osteoporotic vertebral compression fractures.MethodsCT data from a healthy male volunteer were used to construct a three-dimensional finite element model of the L1–L3 vertebrae. A simulated vertebral compression fracture was created at L2, followed by virtual vertebroplasty using two cement distribution patterns: the vertical group (VG) and the inclined group (IG). Stress distribution, maximum von Mises stress in the vertebrae and intervertebral discs, and the maximum displacement of L2 were compared between the two groups.ResultsIn the L2 vertebra, the maximum stress in the VG is reduced under all six loading conditions. VG showed reduced maximum stress in the L1 vertebra during extension, left bending, and left/right rotation. For the L3 vertebra, VG achieved the lowest maximum stress under all loading conditions. In the L1–L2 intervertebral disc, VG resulted in lower maximum stress than IG during flexion, extension, and lateral bending. while in the L2–L3 disc, VG produced the lowest maximum stress under all six conditions. Furthermore, under flexion and extension, the maximum displacement of L2 was smaller in VG compared with IG.ConclusionsThe vertical cement distribution pattern effectively reduces vertebral and intervertebral disc stress and provides greater stability of the fractured vertebra compared with the inclined distribution pattern.